First Report on Tropilaelaps Mercedesae Presence in Georgia: The Mite is Heading Westward! - Janashia Irakli; Uzunov Aleksandar; Chen Chao; Costa Cecilia; Cilia Giovanni (Journal of Apicultural Science)
The Tropilaelaps spp. (Mesostigmata: Laelapidae), an ectoparasitic mite originally associated with such Asian giant honey bees as Apis dorsata, A. breviligula and A. laboriosa, has increasingly become a focus of global concern due to its severe effects on Western honey bee colonies (Apis mellifera) and its recent geographic expansion. This study documents the first reported presence of Tropilaelaps mercedesae in Western Georgia's Samegrelo-Zemo Svaneti region, specifically in seven honey bee colonies (A. mellifera caucasica) from three apiaries. We conducted brood sample inspections, DNA barcoding and morphological measurements to confirm mite identification. Our findings revealed high infestation rates of T. mercedesae, co-infestation with Varroa destructor and notable mite reproductive success. These results underscore the threat posed by T. mercedesae to Georgian apiculture and highlight the potential for further spread across Europe. Immediate action and vigilant monitoring by national and international authorities are crucial to mitigate the impact on beekeeping and agriculture.